Cholecystectomy and adenomatous polyps of the large bowel. Issue 10 (October 1986) - Llamas, K J; Torlach, L G; Ward, M; Bain, C
Abstract : Seventy two patients (39 women) with colonic adenomas were compared with 72 adenoma free controls (39 women) to investigate the possible association between previous cholecystectomy and the subsequent development of adenomas. Data were gathered retrospectively from medical records. Overall there was no significant association between colonic adenomas and previous cholecystectomy. When women are considered separately, however, eight cases and no controls had undergone cholecystectomy (odds ratio infinity lower 95% confidence limits 1.7, p greater than 0.01). No association between previous cholecystectomy and large bowel adenomas was found in men. Four of nine (44.4%) women with right sided colonic adenomas had undergone previous cholecystectomy compared with only three of 23 (13%) women with left sided adenomas.